Implementation of the Murottal Method in Improving the Quality of Reading for Al-Quran Tahfidz Program Students at SMP IT Nurul Azmi Medan - Bangko, Rahmi Fadila Putri; Zailani (Edumaniora : Jurnal Pendidikan dan Humaniora, 2022)
Implementation of the Murottal Method in Improving the Quality of Reading for Students of the Tahfidz Al-Quran Program at SMP IT Nurul Azmi Medan. 2022, Advisor Dr. Zailani, MA. The purpose of this research is to find out whether there is an improvement in the reading quality of the students of the Tahfidz Al-Quran program at SMP IT Nurul Azmi Medan through the implementation of this murottal method. The research method used in this study is a qualitative methodAnd as for the efforts in charge of the program to improve this reading the difficulty of pronouncing the hijaiyah letters when depositing will be corrected again when depositing memorization. In accordance with the rules of correct Tajweed. And as for the efforts in charge of the program to improve this reading, it is done by listening to the verses of the Koran first, then the teacher will mentally recite the readings and letters that are still wrong until students can pronounce them correctly. the difficulty of pronouncing the hijaiyah letters when depositing will be corrected again when depositing memorization. In accordance with the rules of correct Tajweed. And as for the efforts in charge of the program to improve this reading, it is done by listening to the verses of the Koran first, then the teacher will mentally recite the readings and letters that are still wrong until students can pronounce them correctly.